THE EFFECTIVENESS COMBINATION OF PALM KERNEL BIOCHAR AND TITHONIA COMPOST ON IMPROVING HYDROLOGICAL RESPONSE AND CORN YIELD IN ULTISOL - Diah - Listyarini; Endriani Endriani; Frangki Pasaribu (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
The primary objective of this research was to investigate the efficacy of a combination of soil ameliorants, specifically oil palm shell biochar and tithonia compost, in enhancing the hydrological response of Ultisols and increasing corn yields. The study aimed to identify the optimal dosage combination that would significantly impact Ultisol hydrological response and maize yield. The randomized block design (RBD) was utilized to conduct the study. The ameliorant materials consisted of oil palm shell biochar and tithonia compost, which were divided into six treatments and four groups, including without Biochar and compost (p0), 10 tonnes/ha of Biochar (p1), 7.5 tonnes/ha of biochar 2.5 tonnes/ha of compost (p2), 5 tonnes/ha of biochar 5 tonnes/ha of compost (p3), 2.5 tonnes/ha of Biochar + 7.5 tonnes/ha (p4), and 10 tonnes/ha of compost (p5). Soil physical parameters, such as soil organic matter, soil bulk density, total pore space, soil texture, permeability, infiltration rate, and soil infiltration capacity, were monitored during the study. The BNJ test with a 95% confidence level was used to analyze the research data. The result of the study indicated that the p3 treatment (5 tonnes/ha of Biochar and 5 tonnes/ha of compost) and the p4 treatment (7.5 tonnes/ha of compost 2.5 tonnes/ha of Biochar) demonstrated a more significant improvement in infiltration rate and capacity, as well as soil permeability, compared to the other treatments. Moreover, the p3 treatment (5 tonnes/ha of biochar 5 tonnes/ha of compost) was shown to enhance corn yields by 80.53%, while the p4 treatment (2.5 tonnes/ha of biochar 7.5 tonnes/ha of compost) resulted in an 80% increase in yields.Keywords: Biochar; compost; infiltration; palm shells; tithonia; Ultisol